Robotic system education for young children by collaborative‐project‐based learning. Issue 1 (28th November 2019) - Jawaid, Iqra; Javed, Muhammad Yaqoob; Jaffery, Mujtaba H.; Akram, Aftab; Safder, Umair; Hassan, Sarmad
Abstract: This paper presents the fusion of project‐based learning (PBL) and collaborative learning (CL) cohesively, coordinated with sensors and Bluetooth advancements, open‐source programming, and open‐source equipment devices, in a specific microcontroller and installed frameworks designing apply autonomy course for the elementary learners. The major purpose of this study is to evaluate the significance of integrating PBL and CL. The course creates capacities and abilities in critical thinking, problem‐solving, independent learning, collaboration, and specialized technical information. Since PBL alone does not guarantee profoundly talented cooperation, it was supplemented with CL. This structure coordinated course substance and understudy pragmatic accomplishment in a reenacted learning environment. The understudies built a line following and Bluetooth‐controlled robots by actualizing control programming on the "Arduino" open‐source platform, just as utilizing remote interchanges as Arduino offers an instinctive advancement condition and different equipment and programming resources that permit quick improvement of microcontroller‐based ventures. The basic findings of this study work reveal that teaching, learning, and student assessment processes can be improved by using PBL when integrated with CL. The research successfully extends onto another group of learners for preparing similar gadgets under different timelines. In addition, this paper also discusses upon the problem identification, selection of the equipment, circuit design, hardware mounting, and critical analysis of the results acquired from the course through the personal learning experience of the teachers as well as in the form of feedback from the two groups of young learners.